The Board of Directors and Financial Interests - Schmidt, Richard (Academy of Management Journal, 1977)
The article discusses the results of a study pertaining to the dominance of financial interest representation on the boards of directors of nonfinancial corporations. The inside-outside composition aspect of board composition was statistically insignificant as an explanatory variable in relation to corporate economic performance and financial policy. The study concluded that the significance of the affiliations of outside directors should be questioned in relation to the behavior of the industrial corporation.